Talent Management and Teacher Leadership Talent Development in High Performing School in Malaysia - Mohd Izham Mohd Hamzah; Shuhaida Shamsudin (International Journal of Educational Best Practices, 2017)
Researches on the effective leadership reveal that principals in high performing schools aresuccessful in improving schools outcomes through who they are, the strategies they use, as well asthe specific combination and timely implementation and management of these strategies as a resultof the unique contexts in which they work. The present research work tries to explore and confirmthe talent management factors (TMFs) responsible for developing teacher leadership talent (TLT).The proposed TMFs were tested and validated through a sample of 400 teachers of HighPerforming School in Malaysia using Amos 19. Hypotheses were tested at a 95% confidence leveland the Root Mean Square Error of Approximation (RMSEA), Tucker-Lewis Index (TLI) andComparative Fit Index (CFI) were used to test the structural equation model of talent management.The obtained RMSEA value was 0.049, TLI value was 0.942 and CFI value was 0.962 whichindicated a good model fit and appropriateness. Analysis of the results demonstrated that the levelof implementation of talent management falls into the range of being very good and has asignificant relationship with a teacher leadership talent development of the organization in thestudied population. This study is one of very few studies to provide an integrative perspective ofTMFs for developing TLT in high performing school; it adds to the extremely limited number ofempirical studies that have been conducted to investigate talent management in the educationsector and how teacher leaders start as individual contributors and move up into management andleadership roles.